Risk analysis for cooperation policies benefits in reducing the bullwhip effect in a telecom supply chain. (9th January 2012) - Thierry, Caroline; Mahmoudi, Jaouher; Lamothe, Jacques
Supply chain demand is often prone to fluctuations and instability. Known as the 'bullwhip effect', small variations in end–item demand create order and inventory oscillations that amplify from a downstream site to an upstream site. Applying a risk analysis approach, and assuming the bullwhip phenomenon as a constant reality, this paper will present the profits or losses that can accrue from various cooperation policies. The latter are based on planning, information sharing and stock–adjustment strategies adopted by the supply chain actors. The system considered for this research is a four–stage supply chain. To allow risk measures and analysis, a specific discrete–event–simulation system was developed.